Penser l’école à travers le sport (et vice versa). Engagements sportifs et stratégies scolaires des jeunes pongistes chinois - Aurélien Boucher (Cahiers de la Recherche sur l'Education et les Savoirs)
Based on a two-year field study in Chinese high-level sport training centers in the Shandong province, this paper, focused on children, teenagers and youth playing table tennis from 15 to 36 hours a week, aims to show the link between sport involvement and the chances to succeed at national college entrance examinations. It will demonstrate how a sociological study of Chinese sport-study programs provides a better understanding of the Chinese educational system and its inequalities.